Development of software for an information system that points the way using augmented reality technology - Martyshkin, Alexey I.; Bershadskaya, Elena G. (Nexo Revista Científica, 2020)
This paper describes the development process for the map directions information system application utilizing augmented reality technology. The first part of this paper discusses issues related to the research objective formulation. The objective and tasks to be solved are determined. Theoretical information and developments in the subject area are discussed. The second part describes the developed application architecture, the choice of a programming language is explained. The third part expressively addresses the development of algorithms and the application itself. The next section contains instructions for end users. And finally, a summary of the concluded work is given and relevant conclusions are made about the obtained results. It is emphasized that the work leads to the creation of an application for route finding and navigation in augmented reality mode. It is noted that this application can be extended and enhanced by developing versions for other mobile operating systems (for example, iOS and Windows Phone).